Hydrogel compound, preparation method and application

The combination of shell polycan, hydroxytico, and methyl acrocylidized geltic mech glue and sodium glycerol phosphate and functional drugs form a combination of excellent mechanical performance, breathability, and mild -release hydrogel complexes It solves the problem of insufficient mechanical strength and poor breathability of the existing water gel in wound healing, and achieves more effective wound healing effects.

CN119345379AActive Publication Date: 2025-01-24GUANGDONG YUNZHAO MEDICAL TECH CO LTD

Patent Information

Application Number
CN202411423081.6
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-24
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing chitosan hydrogels have problems such as insufficient mechanical strength, poor breathability and unstable drug release in promoting wound healing.

Method used

By selecting chitosan, hydroxyl -bonatrogen, and methyl acrocylidized mech glue, it is selected as a hydrogel matrix, and sodium phosphate sodium phosphate and functional drugs such as marijuana moltols, meticillin, and acetyl water are introduced. Salmonic acid has a composite with excellent mechanical performance, breathability and mild release hydrogel.

Benefits of technology

The excellent mechanical properties, good breathability and stable and long -acting medicinal slow release effect of hydraulic gel complexion, thereby significantly promoting wound healing.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005081396230000091
    Figure BDA0005081396230000091
  • Figure BDA0005081396230000101
    Figure BDA0005081396230000101
  • Figure BDA0005081396230000102
    Figure BDA0005081396230000102
Patent Text Reader

Abstract

The invention discloses a hydrogel compound, a preparation method and application, and belongs to the technical field of hydrogel. The hydrogel compound provided by the invention is prepared from the following raw materials: a hydrogel matrix, sodium glycerophosphate pentahydrate and a functional drug, the hydrogel matrix is prepared from chitosan, hydroxybutyl chitosan and methacrylated gelatin; the functional medicines comprise cannabidiol, tobramycin and acetylsalicylic acid; the hydrogel compound provided by the invention has excellent mechanical properties and water vapor permeability, also has excellent slow release property and wound healing ability, and can be widely applied to preparation of medicines for treating wounds. In addition, the preparation method of the hydrogel compound provided by the invention is simple to operate and beneficial to practical application.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of hydrogels, and in particular relates to a hydrogel composite, a preparation method and an application. Background Art

[0002] Chitosan has the characteristics of biocompatibility, biodegradability, antibacterial and hemostatic properties, and has the function of promoting cells to produce growth factors and forming the environment required for wound healing. It is widely used as a material for preparing hydrogels in the prior art. Hydrogels are three-dimensional networks or interpenetrating networks between solids and liquids. Hydrogels prepared with chitosan as a material also have good biocompatibility, and can be prepared into products such as thermosensitive or photosensitive hydrogels by combining other different components, so that they can be injected or applied to human wounds or defects in the form of solutions, and quickly complete gelation under the temperature of the human body or the irradiation of visible light.

[0003] However, relying solely on the antibacterial hemostatic properties of chitosan and the promotion of cell growth factor production is not enough to effectively promote wound healing, and the existing chitosan hydrogels may have poor air permeability on the basis of good adhesion. In addition, the mechanical strength of the three-dimensional network or interpenetrating network formed by chitosan hydrogels is insufficient, and although the three-dimensional network or interpenetrating network can load drugs to a certain extent to further enhance the corresponding efficacy of the hydrogel, the differences in physical properties such as hydrophilicity and hydrophobicity caused by the structural differences of drug molecules will affect the interaction between drugs, the release rate of drugs, and the degree of efficacy. Summary of the invention

[0004] The purpose of the present invention is to overcome the deficiencies of the above-mentioned prior art and to provide a hydrogel composite having excellent mechanical properties, water vapor permeability, sustained release and wound healing promoting efficacy, a preparation method and application.

[0005] To achieve the above object, in a first aspect of the present invention, the present invention provides a hydrogel composite, the hydrogel composite comprising the following raw materials: a hydrogel matrix, sodium glycerophosphate pentahydrate and a functional drug;

[0006] The hydrogel matrix includes chitosan, hydroxybutyl chitosan and methacryloyl gelatin;

[0007] The functional drugs include cannabidiol, tobramycin and acetylsalicylic acid.

[0008] The hydrogel composite provided by the present invention is compounded by selecting chitosan, hydroxybutyl chitosan and methacryloyl gelatin as a hydrogel matrix, so that the obtained hydrogel composite has good mechanical properties under the premise of having basic adhesion performance; Specifically, it has excellent tensile strength and elongation at break; And, the use of chitosan, hydroxybutyl chitosan and methacryloyl gelatin compound can also make the obtained hydrogel composite have excellent water vapor permeability, thereby further improving the antibacterial property of the product and accelerating wound healing. At the same time, the present invention introduces sodium glycerophosphate pentahydrate, which can provide temperature sensitivity for the hydrogel composite on the one hand, and can also help the hydrogel matrix to be quickly cross-linked into a network structure on the other hand, so as to efficiently load the drug and realize the sustained release of the drug. In addition, the present invention selects functional drugs including cannabidiol, tobramycin and acetylsalicylic acid. On the one hand, the combination of the three can better achieve antibacterial, hemostatic, anti-inflammatory and cell growth promotion, thereby achieving a better effect of promoting wound healing; on the other hand, the three can have a strong hydrogen bond connection with the hydrogel matrix and sodium glycerophosphate pentahydrate, thereby achieving a stable and long-lasting sustained release effect, and enhancing the promotion of wound healing.

[0009] As a preferred embodiment of the hydrogel composite of the present invention, the hydrogel matrix comprises the following components in parts by weight: 1 part of chitosan, 0.2-0.8 parts of hydroxybutyl chitosan, and 0.04-0.15 parts of methacryloyl gelatin.

[0010] Exemplarily, hydroxybutyl chitosan can be any point value or any two point range value between 0.2-0.8 parts, such as 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, etc.; methacryloyl gelatin can be any point value or any two point range value between 0.04-0.15 parts, such as 0.04 parts, 0.06 parts, 0.08 parts, 0.10 parts, 0.12 parts, 0.14 parts, 0.15 parts, etc.

[0011] The present invention has found that the proportions of chitosan, hydroxybutyl chitosan and methacryloyl gelatin in the hydrogel matrix not only affect the hydrophilicity and hydrophobicity of the hydrogel matrix as a whole, thereby affecting the subsequent loading effect on the drug and the sustained release effect of the drug, but also affect the mechanical properties and water vapor permeability of the prepared hydrogel composite; when the proportions of chitosan, hydroxybutyl chitosan and methacryloyl gelatin in the hydrogel matrix are further selected to be within the above range, the comprehensive performance of the obtained hydrogel composite is better.

[0012] Preferably, the hydrogel matrix comprises the following components in parts by mass: 1 part of chitosan, 0.4-0.6 parts of hydroxybutyl chitosan, and 0.08-0.1 parts of methacryloyl gelatin.

[0013] The present invention has found that when the proportions of chitosan, hydroxybutyl chitosan and methacryloyl gelatin in the hydrogel matrix are further selected to be within the above range, the comprehensive performance of the obtained hydrogel composite is more excellent.

[0014] As a preferred embodiment of the hydrogel composite of the present invention, the chitosan satisfies at least one of the following conditions:

[0015] a. The degree of deacetylation of the chitosan is 75-100%;

[0016] b. The weight average molecular weight of the chitosan is 50,000-300,000.

[0017] It should be noted that chitosan can be homemade or a conventional commercial product.

[0018] The test method of the deacetylation degree of chitosan is as follows: accurately weigh 0.3g of chitosan dried to constant weight and place it in a 250mL conical flask, add 30mL of standard 0.1mol / L hydrochloric acid solution, stir at room temperature until dissolved, add 10mL of distilled water to dilute, and add 3 drops of 1% I-KI reagent. Titrate with 0.1mol / L sodium hydroxide standard solution until a bright purple granular precipitate appears, which is the titration end point. Repeat three times and take the average value, and calculate the deacetylation degree according to formula (1) and formula (2):

[0019] Formula (1): NH2% = [(C1V1-C2V2)*0.016 / G]*100; where C1 mol / L is the concentration of the hydrochloric acid standard solution, C2 mol / L is the concentration of the sodium hydroxide standard solution, V1 mL is the volume of the hydrochloric acid standard solution added, V2 mL is the volume of the sodium hydroxide standard solution consumed, and G g is the sample mass;

[0020] Formula (2): Deacetylation degree % = NH2% / 9.94%*100.

[0021] The weight average molecular weight of chitosan is determined by high performance gel permeation chromatography (GPC).

[0022] Exemplarily, the deacetylation degree of the chitosan can be any point value or any two point range values ​​between 75-100%, such as 75%, 76%, 78%, 80%, 82%, 84%, 86%, 88%, 90%, 92%, 94%, 96%, 98%, 100%, etc. The weight average molecular weight of the chitosan can be any point value or any two point range values ​​between 50,000 and 300,000, such as 50,000, 60,000, 80,000, 100,000, 120,000, 140,000, 160,000, 180,000, 200,000, 220,000, 240,000, 260,000, 280,000, 300,000, etc.

[0023] The present invention has found that the deacetylation degree and weight-average molecular weight of chitosan not only affect the water solubility of chitosan, but also affect the cross-linking effect, thereby affecting the water vapor permeability, sustained release and interaction with drugs of the hydrogel composite; when the deacetylation degree and weight-average molecular weight of chitosan are further selected to be within the above range, the obtained hydrogel composite has better mechanical properties, better air permeability, and better sustained release and wound healing effects.

[0024] As a preferred embodiment of the hydrogel composite of the present invention, the chitosan satisfies at least one of the following conditions:

[0025] c. The degree of deacetylation of the chitosan is 85-95%;

[0026] d. The weight average molecular weight of the chitosan is 100,000-200,000.

[0027] The present invention has found that when the deacetylation degree and weight average molecular weight of chitosan are further selected to be within the above ranges, the comprehensive performance of the obtained hydrogel composite is better.

[0028] As a preferred embodiment of the hydrogel composite of the present invention, the degree of substitution of the hydroxybutyl chitosan is 1.0-1.25.

[0029] It should be noted that the degree of substitution of hydroxybutyl chitosan is obtained by elemental analysis.

[0030] Exemplarily, the degree of substitution of the hydroxybutyl chitosan can be any point value or any two point range values ​​between 1.0-1.25, for example, it can be 1.0, 1.02, 1.04, 1.06, 1.08, 1.10, 1.12, 1.14, 1.16, 1.18, 1.20, 1.22, 1.24, 1.25, etc.

[0031] The present invention finds that the degree of substitution of hydroxybutyl chitosan affects its own water solubility and ability to form hydrogel, thereby affecting the mechanical properties and air permeability of the hydrogel composite material, and also affecting its loading effect on drugs, thereby affecting the sustained release of drugs and the promotion of wound healing.

[0032] As a preferred embodiment of the hydrogel composite of the present invention, the degree of substitution of the methacryloyl gelatin is ≥80%.

[0033] It should be noted that the degree of substitution of methacryloyl gelatin is measured by nuclear magnetic resonance spectroscopy.

[0034] Exemplarily, the degree of substitution of the methacryloyl gelatin can be any point value or any two-point range value between ≥80%, for example, it can be 80-90%, or it can be 80%, 81%, 82%, 83%, 84%, 85%, 86%, 87%, 88%, 89%, 90%, etc.

[0035] The present invention has found that the degree of substitution of methacryloyl gelatin not only affects its cross-linking properties, but also affects its mechanical properties. When the degree of substitution of methacryloyl gelatin is further selected to be ≥80%, the comprehensive performance of the obtained product is more excellent.

[0036] As a preferred embodiment of the hydrogel complex of the present invention, the functional drug comprises the following components in parts by weight: 1 part of cannabidiol, 0.2-0.9 parts of tobramycin, and 1-6 parts of acetylsalicylic acid.

[0037] Exemplarily, the tobramycin can be any point value or any range value between 0.2-0.9 parts, such as 0.2 parts, 0.3 parts, 0.4 parts, 0.5 parts, 0.6 parts, 0.7 parts, 0.8 parts, 0.9 parts, etc.; acetylsalicylic acid can be any point value or any range value between 1-6 parts, such as 1 part, 2 parts, 3 parts, 4 parts, 5 parts, 6 parts, etc.

[0038] Preferably, the functional drug comprises the following components in parts by mass: 1 part of cannabidiol, 0.4-0.6 parts of tobramycin, and 2-4 parts of acetylsalicylic acid.

[0039] Cannabidiol has bactericidal, analgesic, anti-inflammatory, antioxidant, and anti-anxiety functions, and has rich downstream application scenarios. Its main value is reflected in the medical aspect. Tobramycin is an aminoglycoside antibiotic that has good antibacterial effects on most bacteria. It can be used for infections caused by a variety of sensitive bacteria and has good anti-inflammatory effects. The present invention has found that the mass ratio between cannabidiol and tobramycin affects the comprehensive properties of the hydrogel composite, especially the antibacterial, anti-inflammatory, hemostatic and wound healing effects. Acetylsalicylic acid, also known as aspirin, has antipyretic, analgesic, anti-inflammatory, anti-rheumatic and anti-platelet aggregation pharmacological effects, but excessive use can also produce side effects, such as allergic reactions, liver damage and gastrointestinal symptoms, etc. Gastrointestinal symptoms are the most common adverse reactions of aspirin, and the more common symptoms are nausea, vomiting, upper abdominal discomfort or pain, etc. The present invention has found that in the hydrogel system of the present invention, cannabidiol, tobramycin and acetylsalicylic acid have a good compounding effect, and have excellent antibacterial, hemostatic and anti-inflammatory effects, thereby being able to quickly promote wound healing; especially when the proportions of cannabidiol, tobramycin and acetylsalicylic acid are selected within the range given in the present invention, the comprehensive performance of the obtained hydrogel composite is more excellent.

[0040] In the second aspect of the present invention, the present invention provides a method for preparing the hydrogel composite, which comprises the following steps: mixing a hydrogel matrix solution, a sodium glycerophosphate pentahydrate solution, and a functional drug solution in sequence and stirring them into a gel to obtain a hydrogel composite.

[0041] The preparation method of the hydrogel composite provided by the invention is simple to operate and is conducive to practical production and application.

[0042] As a preferred embodiment of the preparation method of the present invention, the mass percentage of the solute in the hydrogel matrix solution is 1-5%.

[0043] As a preferred embodiment of the preparation method of the present invention, the mass percentage of the solute in the sodium glycerophosphate pentahydrate solution is 30-40%.

[0044] As a preferred embodiment of the preparation method of the present invention, the concentration of the solute in the functional drug solution is 0.02-0.9 mol / L.

[0045] The present invention has found that when the mass percentage of the solute in the above solution or the molar concentration of the solute is further selected to be within the above range, the hydrogel complex can be formed by a good reaction.

[0046] As a preferred embodiment of the preparation method of the present invention, the volume ratio of the hydrogel matrix solution, sodium glycerophosphate pentahydrate solution and functional drug solution is hydrogel matrix solution: sodium glycerophosphate pentahydrate solution: functional drug solution = 1: (0.1-0.4): (0.1-1.5).

[0047] The present invention has found that when the volume ratio between the solutions is further selected to be within the above range, a good gelation reaction can be achieved in a better manner in accordance with the preferred solute mass percentage range or solute molar concentration range.

[0048] As a preferred embodiment of the preparation method of the present invention, the solvent of the hydrogel matrix solution is an acetic acid aqueous solution with a mass percentage of 1-5%.

[0049] As a preferred embodiment of the preparation method of the present invention, the solvent of the sodium glycerophosphate pentahydrate solution is deionized water.

[0050] As a preferred embodiment of the preparation method of the present invention, the solvent of the functional drug solution is ethanol aqueous solution.

[0051] Preferably, the mass percentage of ethanol in the ethanol aqueous solution is 30-70%.

[0052] As a preferred embodiment of the preparation method of the present invention, the stirring temperature is 30-50°C.

[0053] As a preferred embodiment of the preparation method of the present invention, the mixture is stirred sequentially at a speed of 300-500 rpm for 5-10 minutes after each solution is added to ensure sufficient mixing.

[0054] In the third aspect of the present invention, the present invention provides use of the hydrogel complex in preparing a drug for treating wounds.

[0055] The hydrogel composite provided by the present invention can not only effectively inhibit bacteria, but also has the effects of hemostasis, analgesia and anti-inflammation, and therefore can be widely used in the treatment of trauma.

[0056] Compared with the prior art, the present invention has the following beneficial effects:

[0057] The hydrogel composite provided by the present invention is compounded by selecting chitosan, hydroxybutyl chitosan and methacryloyl gelatin as a hydrogel matrix, so that the obtained hydrogel composite has good mechanical properties under the premise of having basic adhesion performance; Specifically, it has excellent tensile strength and elongation at break; And, the use of chitosan, hydroxybutyl chitosan and methacryloyl gelatin compound can also make the obtained hydrogel composite have excellent permeability to water vapor, thereby further improving the antibacterial property of the product and accelerating the healing of wounds. At the same time, the present invention introduces sodium glycerophosphate pentahydrate, which can provide temperature sensitivity for the hydrogel composite on the one hand, and can also help the hydrogel matrix to be quickly cross-linked into a network structure on the other hand, so as to efficiently load the drug and realize the sustained release of the drug. In addition, the present invention selects cannabidiol, tobramycin and acetylsalicylic acid as functional drugs. On the one hand, the three compounding can better achieve antibacterial, hemostatic, anti-inflammatory and promote cell growth, thereby achieving a more excellent effect of promoting wound healing; on the other hand, the three can have a strong hydrogen bond connection with the hydrogel matrix and sodium glycerophosphate pentahydrate, thereby being able to achieve a stable and long-lasting sustained release effect, and strengthening the promotion of wound healing. In addition, the preparation method of the hydrogel composite provided by the present invention is simple to operate, which is conducive to actual production. BRIEF DESCRIPTION OF THE DRAWINGS

[0058] Figure 1 This is a photograph of the hydrogel composite prepared in Example 1;

[0059] Figure 2 This is a photograph of the inverted state of the hydrogel composite prepared in Example 1. DETAILED DESCRIPTION

[0060] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.

[0061] Unless otherwise specified, the reagents, methods and equipment used in the present invention are conventional reagents, methods and equipment in the art.

[0062] Chitosan 1: The deacetylation degree is 95%, the weight average molecular weight is 100,000, and it is homemade. The preparation method comprises the following steps: 5 g of chitosan is hydrolyzed in 50 mL of 10 mol / L sodium hydroxide aqueous solution at a hydrolysis temperature of 110° C. and a hydrolysis time of 1.8 h. After the hydrolysis is completed, the chitosan is filtered, washed, and dried to obtain a product with a deacetylation degree of 95%; the dried product is dissolved in 145 mL of 0.34 mol / L acetic acid solution and heated to 60° C., then 7.5 mL of hydrogen peroxide solution is added and reacted for 130 min. After the reaction is completed, the product is cooled to room temperature, and a sodium hydroxide solution is added dropwise with stirring until the pH value is 8.5, and then filtered, the filter residue is collected, washed, and dried; chitosan 1 is obtained.

[0063] Chitosan 2: Deacetylation degree is 85%, weight average molecular weight is 200,000, homemade, the preparation method is different from chitosan 1 in that the hydrolysis temperature and time are adjusted to achieve 85% deacetylation degree, and the time of adding hydrogen peroxide reaction is adjusted to achieve 200,000 weight average molecular weight.

[0064] Chitosan 3: Deacetylation degree is 75%, weight average molecular weight is 80,000, homemade, the difference between the preparation method and chitosan 1 is that the hydrolysis temperature and time are adjusted to achieve 75% deacetylation degree, and the time of adding hydrogen peroxide reaction is adjusted to achieve 80,000 weight average molecular weight.

[0065] Chitosan 4: Deacetylation degree is 98%, weight average molecular weight is 300,000, homemade, the preparation method is different from chitosan 1 in that the hydrolysis temperature and time are adjusted to achieve 98% deacetylation degree, and the time of adding hydrogen peroxide reaction is adjusted to achieve 300,000 weight average molecular weight.

[0066] Hydroxybutyl chitosan 1: The degree of substitution is 1.05, and it is homemade. The preparation method includes the following steps: weigh 1g chitosan and disperse it in 10mL 50% NaOH solution for alkalization treatment, stir it at room temperature for 24h under nitrogen protection, then filter it, collect the filter residue and add 10mL isopropanol aqueous solution (in the isopropanol aqueous solution, the volume ratio of isopropanol and water is 15:5) and stir it for 24h until the alkalized chitosan is completely dispersed in the isopropanol system. Then measure 12mL 1,2-butylene oxide and drop it into the reaction container, and react at room temperature for 1h. After the reaction is completed, add 10% HCl solution to the reaction solution to adjust the pH of the system to neutral. When the mixed solution becomes clear and transparent, filter and collect the filtrate and precipitate it with alcohol overnight, then centrifuge it, collect the solid precipitate and dry it to obtain hydroxybutyl chitosan 1.

[0067] Hydroxybutyl chitosan 2: The degree of substitution is 1.20, and it is homemade. The difference between the preparation method and that of hydroxybutyl chitosan 1 is that the degree of substitution of 1.20 is achieved by adjusting the volume ratio of isopropanol and water in the isopropanol aqueous solution, the amount of 1,2-butylene oxide, and the reaction temperature and time.

[0068] Hydroxybutyl chitosan 3: The degree of substitution is 0.9, and it is homemade. The difference between the preparation method and that of hydroxybutyl chitosan 1 is that the degree of substitution is 0.9 by adjusting the volume ratio of isopropanol and water in the isopropanol aqueous solution, the amount of 1,2-butylene oxide, and the reaction temperature and time.

[0069] Hydroxybutyl chitosan 4: The degree of substitution is 1.3, and it is homemade. The difference between the preparation method and that of hydroxybutyl chitosan 1 is that the degree of substitution is 1.30 by adjusting the volume ratio of isopropanol and water in the isopropanol aqueous solution, the amount of 1,2-butylene oxide, and the reaction temperature and time.

[0070] Methacryloyl gelatin 1: degree of substitution 85%, Xi'an Qiyue Biotechnology Co., Ltd.

[0071] Methacryloyl gelatin 2: degree of substitution 75%, Xi'an Qiyue Biotechnology Co., Ltd.

[0072] Example 1

[0073] An embodiment of the present invention provides a hydrogel composite, and a method for preparing the hydrogel composite comprises the following steps:

[0074] (1) Preparation of hydrogel matrix solution: 1 part chitosan 1, 0.4 parts hydroxybutyl chitosan 1, and 0.08 parts methacryloyl gelatin 1 were weighed and dissolved in 1% by weight acetic acid aqueous solution to prepare a hydrogel matrix solution with a solute weight percentage of 2%;

[0075] (2) Preparation of sodium glycerophosphate pentahydrate solution: dissolving sodium glycerophosphate pentahydrate in a deionized water solution to prepare a sodium glycerophosphate pentahydrate solution having a solute mass percentage of 35%;

[0076] (3) Preparation of functional drug solution: 1 part of cannabidiol, 0.4 parts of tobramycin and 2 parts of acetylsalicylic acid were dissolved in 50% ethanol aqueous solution to prepare a functional solution with a temperature of 40-45° C. and a solute concentration of 0.24 mol / L;

[0077] (4) Preparation of hydrogel complex: 1 mL of hydrogel matrix solution was placed in a container, the temperature of the container was controlled at 40-45°C, 0.2 mL of sodium glycerophosphate pentahydrate solution was added, and the mixture was stirred at 400 rpm for 5 min, followed by addition of 0.24 mL of functional drug solution, stirring at 400 rpm for 5 min, and then standing at room temperature for 1 min to form a hydrogel, thereby obtaining a hydrogel complex.

[0078] The schematic diagram of the gel formation of the prepared hydrogel composite is as follows: Figure 1 As shown, the inverted state after gelation is as follows Figure 2 shown.

[0079] Example 2

[0080] An embodiment of the present invention provides a hydrogel composite, and a method for preparing the hydrogel composite comprises the following steps:

[0081] (1) Preparation of hydrogel matrix solution: 1 part chitosan 1, 0.6 parts hydroxybutyl chitosan 1, and 0.1 parts methacryloyl gelatin 1 were weighed and dissolved in a 1% by weight acetic acid aqueous solution to prepare a hydrogel matrix solution with a solute weight percentage of 5%;

[0082] (2) Preparation of sodium glycerophosphate pentahydrate solution: dissolving sodium glycerophosphate pentahydrate in a deionized water solution to prepare a sodium glycerophosphate pentahydrate solution having a solute mass percentage of 40%;

[0083] (3) Preparation of functional drug solution: 1 part of cannabidiol, 0.4 parts of tobramycin and 2 parts of acetylsalicylic acid were dissolved in 50% ethanol aqueous solution to prepare a functional solution with a temperature of 40-45° C. and a solute concentration of 0.48 mol / L;

[0084] (4) Preparation of hydrogel complex: 1 mL of hydrogel matrix solution was placed in a container, the temperature of the container was controlled at 40-45°C, 0.2 mL of sodium glycerophosphate pentahydrate solution was added, and the mixture was stirred at 400 rpm for 5 min, followed by addition of 0.48 mL of functional drug solution, stirring at 400 rpm for 5 min, and then standing at room temperature for 1 min to form a hydrogel, thereby obtaining a hydrogel complex.

[0085] Example 3-15

[0086] The embodiment of the present invention provides a hydrogel composite, the difference between the hydrogel composite and embodiment 1 is in Table 1, except for Table 1, the rest is consistent with embodiment 1; Table 1 is mass parts; specifically, the difference between embodiments 3-12 and embodiment 1 is that the raw materials and the number of raw materials used in the preparation of the hydrogel matrix solution in step (1) are changed, and the difference between embodiments 13-15 and embodiment 1 is that the number of functional drugs in step (3) is changed;

[0087] Table 1

[0088]

[0089]

[0090] Comparative Examples 1-9

[0091] The comparative examples of the present invention provide a hydrogel composite, the difference between the hydrogel composite and Example 1 is in Table 2, except for Table 2, the rest is consistent with Example 1; Table 2 is weight parts; specifically, the difference between Comparative Examples 1-4 and Example 1 is that the raw materials used in the preparation of the hydrogel matrix solution in step (1) are changed, and the difference between Comparative Examples 5-9 and Example 1 is that the raw materials of the functional drug in step (3) are changed;

[0092] Table 2

[0093]

[0094] Effect example

[0095] The effect examples of the present invention verify the performance of the hydrogel composites prepared in Examples 1-15 and Comparative Examples 1-9, including the following aspects:

[0096] 1. Mechanical properties test

[0097] The hydrogel composites in the embodiments and comparative examples were prepared into a dumbbell shape with a total length of 30 mm and a width of 10 mm, with dumbbell parts on both sides and a sample part in the middle. The sample length was 20 mm, the sample width (i.e., the shortest distance in the middle of the dumbbell) was 10 mm, and the sample thickness was 1 mm. The tensile rate was set to 25 mm / min, and a WDW-50 microcomputer-controlled electronic universal testing machine was used to measure the tension (N) and elongation (mm) of the sample at break. Each sample was repeated 5 times and the average value was taken to calculate the tensile strength and elongation at break of the hydrogel dressing;

[0098] The tensile strength (σ) of the hydrogel is the ratio of the maximum tensile stress of the gel to the cross-sectional area of ​​the sample, that is, σ is the tensile strength in MPa, F max is the maximum tensile stress N, A is the cross-sectional area of ​​the sample (sample width × sample thickness) mm 2; Elongation at break (ε) is the ratio of the deformation length of the sample to the initial length when it is stretched to break, that is, ε (%) is the elongation at break, L0 and L max are the initial and fracture lengths of the sample, respectively;

[0099] The results are shown in Table 3.

[0100] 2. Water vapor permeability

[0101] The water vapor permeability test of the prepared hydrogel composite was carried out according to the American material performance test standard ASTM method E96-00, specifically:

[0102] First, add 4 mL of distilled water to a 14 mm diameter open vial, then cut the gel complex into 17 mm discs, cover the vial mouth (cover the vial completely), seal the seams with vaseline and sealing film, and weigh. Take a desiccator and add saturated ammonium sulfate solution, put the vial into the desiccator, cover it with a lid, and put it in a 37°C constant temperature drying oven for 24 hours before weighing again;

[0103] The results are shown in Table 3.

[0104] 3. Drug release performance

[0105] Take 0.5g of the hydrogel complex prepared in the embodiment and the comparative example respectively in a conical flask, add 50mL of phosphate buffer solution (0.01mol / L, containing 0.2% SDS) with a pH of 6.8, and test at 37°C and 100rpm constant temperature oscillation, measure 2mL of sample at preset time points (specifically 0.5h, 1h, 2h, 3h, 5h, 8h, 12h, 16h, 25h, 30h), and supplement 2mL of freshly prepared phosphate buffer. Then, the contents of cannabidiol, tobramycin and acetylsalicylic acid in the sample were detected by high performance liquid chromatography and recorded, so as to calculate the cumulative drug release rate, the cumulative drug release rate = (initial drug content - real-time drug content) / initial drug content × 100%, and the cumulative drug release rate obtained by the test at 25h is recorded in Table 1.

[0106] 4. Biocompatibility testing

[0107] The test was conducted with reference to GB / T 16886.5-2003, wherein the biological toxicity score is: no cytotoxicity (0), slight cytotoxicity (1), moderate cytotoxicity (2), and severe cytotoxicity (3); the test results are shown in Table 3.

[0108] 5. Performance of promoting wound healing

[0109] 1) Take 125 SPF rats (BALB / c, female, 6 weeks, weighing 25±4g), and after one week of adaptive feeding, perform hair removal treatment the day before making the trauma model. Anesthetize the mice with an animal anesthesia machine and fix them on the operating table. First, use hair clippers to remove most of the hair on the back of the mice, then use a cotton swab soaked in depilatory cream to wipe the hair-cut area, leave it for a few minutes, and then use a cotton ball to wipe off the excess depilatory cream, and use a clean cotton ball dipped in 0.9% saline to wipe the skin of the depilatory area, and wipe off the residual depilatory cream on the skin to prevent burns to the skin. After wiping, use a clean cotton ball to dry the skin of the depilatory area;

[0110] 2) Establishing a full-thickness skin wound model on the back of mice: The depilated mice were anesthetized with an animal anesthesia machine and fixed on the operating table. After the skin was disinfected with alcohol, a circular full-thickness skin wound with an area of ​​1×1 cm was made on the back with a sterile surgical instrument. The mice were randomly divided into 25 groups, with an average of 5 mice in each group, corresponding to the numbers of Examples 1-15, Comparative Examples 1-9 and the blank group, respectively;

[0111] 3) In the blank group, 100 μL of sterile PBS was dripped onto the skin wound surface, and then the wound edge was fixed with sterile medical transparent fixing tape; in the other groups, the hydrogel complex was adhered to the wound surface, and the wound edge was fixed with sterile medical transparent fixing tape, and finally the animals were raised in separate cages according to the welfare requirements of small animals.

[0112] 4) On days 1, 4, 7, and 14, the mice were anesthetized with isoflurane, and the wounds were photographed to calculate the area. When calculating the wound healing rate, it was necessary to take photos of the back wound at each time point, calculate its area using ImageJ software, and calculate the wound healing rate according to the formula: wound healing rate = (original wound area - current measured area) / original wound area * 100%;

[0113] The results are shown in Table 3.

[0114] Table 3

[0115]

[0116]

[0117] It can be seen from Table 3 that when the technical solution provided by the present invention is adopted, the obtained hydrogel composite has good mechanical properties, water vapor permeability, sustained release performance and the ability to promote wound healing, and the obtained hydrogel composite also has good biocompatibility and excellent adhesion performance. The peel force obtained by the test according to the standard "GB / T2791-1995_Adhesive T peel strength test method flexible material to flexible material" is 28.7kg·m / S 2Specifically, the obtained hydrogel composite has a tensile strength of more than 30.4 MPa, an elongation at break of more than 129%, and a water vapor permeability of 0.35 g / cm 2 / 24h or more, the 25h cumulative drug release rate is below 46%, the wound healing rate on the 4th day is above 42%, and the wound healing rate on the 14th day is above 90%.

[0118] It can be seen from Example 1 and Comparative Examples 1-3 that the components in the hydrogel matrix of the present invention are indispensable. When any one of the components is not added in Comparative Examples 1-3, the obtained product not only has a significant decrease in mechanical properties, but also shows a significant downward trend in water vapor permeability, and the sustained release effect of the loaded drug is also poor, resulting in a decrease in the overall effect when it is subsequently applied to wound healing; it can be seen from Example 1 and Comparative Example 4 that when similar components are used to replace the components in the present invention, the effect of the present invention cannot be achieved; it can be seen from Examples 1 and 2-12 that the parameters of chitosan, hydroxybutyl chitosan and methacryloyl gelatin provided by the present invention and the number of the three added will also have a certain impact on the comprehensive performance of the product. When the parameters of chitosan, hydroxybutyl chitosan and methacryloyl gelatin and the number of the three are further selected within the preferred range of the present invention, the tensile strength of the obtained hydrogel composite is above 30.4MPa, the elongation at break is above 138%, and the water vapor permeability is 0.41g / cm 2 / 24h or more, the 25h cumulative drug release rate is below 36%, the wound healing rate on the 4th day is above 53%, and the wound healing rate on the 14th day is 100%.

[0119] It can be seen from Example 1 and Comparative Example 9 that when cannabidiol, tobramycin and acetylsalicylic acid are introduced into the hydrogel matrix of the present invention, the effect of promoting wound healing of the product can be significantly improved; it can be seen from Example 1 and Comparative Examples 5-7 that cannabidiol, tobramycin and acetylsalicylic acid have excellent synergistic effects in the hydrogel system of the present invention. When the total amount of the drug is kept unchanged, no matter which substance is reduced, the ability of the obtained product to promote wound healing is significantly reduced; it can be seen from Example 1 and Comparative Example 8 that when other substances with similar effects are used to replace the components of the present invention, the effect of the present invention cannot be achieved; it can be seen from Example 1 and Examples 13-15 that the proportions of cannabidiol, tobramycin and acetylsalicylic acid will also affect the ability of the product to promote wound healing. When the proportions of the three are further selected within the preferred range of the present invention, the wound healing rate obtained is above 54% on the 4th day, and the healing rate can reach 100% on the 14th day.

[0120] Finally, it should be noted that the above embodiments are intended to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention may be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.

Claims

1. A hydrogel composite, characterized in that: The hydrogel complex comprises the following raw materials: a hydrogel matrix, sodium glycerophosphate pentahydrate and a functional drug; The hydrogel matrix includes chitosan, hydroxybutyl chitosan and methacryloyl gelatin; The functional drugs include cannabidiol, tobramycin and acetylsalicylic acid.

2. The hydrogel composite according to claim 1, characterized in that The hydrogel matrix comprises the following components in parts by weight: 1 part of chitosan, 0.2-0.8 parts of hydroxybutyl chitosan, and 0.04-0.15 parts of methacryloyl gelatin.

3. The hydrogel composite according to claim 2, characterized in that The hydrogel matrix comprises the following components in parts by weight: 1 part of chitosan, 0.4-0.6 parts of hydroxybutyl chitosan, and 0.08-0.1 parts of methacryloyl gelatin.

4. The hydrogel composite according to claim 1, characterized in that The chitosan satisfies at least one of the following: a. The degree of deacetylation of the chitosan is 75-100%; b. The weight average molecular weight of the chitosan is 50,000-300,000.

5. The hydrogel composite according to claim 4, characterized in that The chitosan satisfies at least one of the following: c. The degree of deacetylation of the chitosan is 85-95%; d. The weight average molecular weight of the chitosan is 100,000-200,000.

6. The hydrogel composite according to claim 1, characterized in that The degree of substitution of the hydroxybutyl chitosan is 1.0-1.

25.

7. The hydrogel composite according to claim 1, characterized in that The substitution degree of the methacryloyl gelatin is ≥80%.

8. The hydrogel composite according to claim 1, characterized in that The functional medicine comprises the following components in parts by mass: 1 part of cannabidiol, 0.2-0.9 parts of tobramycin, and 1-6 parts of acetylsalicylic acid.

9. The hydrogel composite according to claim 8, characterized in that The functional medicine comprises the following components in parts by mass: 1 part of cannabidiol, 0.4-0.6 parts of tobramycin, and 2-4 parts of acetylsalicylic acid.

10. The method for preparing the hydrogel composite according to any one of claims 1 to 9, characterized in that: The preparation method comprises the following steps: The hydrogel matrix solution, the sodium glycerophosphate pentahydrate solution and the functional drug solution are sequentially mixed and stirred into gel to obtain a hydrogel composite.

11. The preparation method according to claim 10, characterized in that: Satisfy at least one of the following: e. The mass percentage of the solute in the hydrogel matrix solution is 1-5%; f. The mass percentage of the solute in the sodium glycerophosphate pentahydrate solution is 30-40%; g. The concentration of the solute in the functional drug solution is 0.02-0.9 mol / L.

12. The preparation method according to claim 10, characterized in that: The volume ratio of the hydrogel matrix solution, sodium glycerophosphate pentahydrate solution and functional drug solution is hydrogel matrix solution: sodium glycerophosphate pentahydrate solution: functional drug solution = 1: (0.1-0.4): (0.1-1.5).

13. The preparation method according to claim 10, characterized in that: Satisfy at least one of the following: h. The solvent of the hydrogel matrix solution is 1-5% by mass of an acetic acid aqueous solution; i. The solvent of the sodium glycerophosphate pentahydrate solution is deionized water; j. The solvent of the functional drug solution is ethanol aqueous solution.

14. The preparation method according to claim 10, characterized in that: The stirring temperature is 30-50°C.

15. Use of the hydrogel complex according to any one of claims 1 to 9 in preparing a drug for treating trauma.

Citation Information

Patent Citations

  • Chitosan medicine carrying temperature-sensitive hydrogel and preparation method and application thereof

    CN104958252A

  • Hydroxybutyl chitosan haemostatic gel with temperature sensitivity and application thereof

    CN107362386A

  • Hydrogel dressing as well as preparation method and application thereof

    CN118045221A

  • Hydrogel wound dressing and preparation method thereof

    CN118490873A

  • Use of cannabidiol in combination with antibiotics

    US20220183997A1

Cited By

  • Oxidized konjac glucomannan and hydrazide hyaluronic acid composite hydrogel as well as preparation method and application thereof

    CN120459361A

  • Oxidized konjac gum and hydrazide hyaluronic acid composite hydrogel, and preparation method and application thereof

    CN120459361B

  • Composite hydrogel as well as preparation method and application thereof

    CN120514919A

  • Cannabidiol wrapped wound patch and preparation method thereof

    CN121154885A